Analisis Faktor Yang Mempengaruhi Intensi Kewirausahaan Siswa Jurusan Otomatisasi Tata Kelola Perkantoran SMKN 1 Surabaya - Vindi Kusuma Wardani; Jaka Nugraha (Edunusa: Journal of Economics and Business Education, 2021)
The number of unemployed as of February 2021 based on education graduates increased by a percentage of 26.3% which reached 8,746,008 unemployed people. The high unemployment rate for SMK graduates is 2,089,137 people. Therefore, students must also be prepared to be able to have the ability and skills in entrepreneurship. This research is included in quantitative descriptive research with the aim of analyzing what factors can influence entrepreneurial intentions in class XI and XII students majoring in office management automation at SMKN 1 Surabaya. The factors that can influence the entrepreneurial intention of class XI and XII students of SMKN 1 Surabaya are entrepreneurship education with a percentage of 51.861%, family environment with a percentage of 17.067%, mindset with a percentage of 10.835%, behavior with a percentage of 9.336%%, ability with a percentage of 6.249 % , and confidence with a percentage value of 4.652%. The factors that dominate the intention of class XI and XII students of SMKN Surabaya in entrepreneurship are entrepreneurship education with a percentage value of 51.861% and the family environment with a percentage value of 17.067%